Cellular and Molecular Mechanisms of the Production of Free Radicals during Exercise and Their Function on Skeletal Muscles - Fatemeh Heyat (Fasa University of Medical Sciences, 2017)
Physical activity is an integral part of human life. Among significant biological changes during physical activity are increase of metabolism and production of free radicals. Free radical can be defined as molecule or molecular fragments containing unpaired electron in the outer orbital, which react with nearby molecules to obtain stability. These highly reactive molecules have various deleterious effects, such as reduced force generation and increased muscle atrophy. There is evidence that ROS produced during exercise has positive adaptation effects. ROS production leads to increased expression of the anti-oxidants. These molecules, by neutralizing free radicals, neutralize the negative effects of ROS. In addition, exercise-induced ROS leads to the expression of PGC-1α  protein, having a significant impact on various aspects of cell metabolism, mitochondrial biogenesis and cellular respiration as well as metabolism of fat and glucose. This paper provides an overview of the evidence to date on the effects of ROS on exercising muscle. These aspects include the sources of ROS, their positive and negative cellular effects,  role of antioxidants, and ROS-dependent adaptations of muscle cells in response to physical exercise